2003
DOI: 10.1577/1548-8659(2003)132<0275:rvtapo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Relative Vulnerability to Avian Predation of Juvenile Salmonids Tagged with Passive Integrated Transponders in the Columbia River Estuary, 1998–2000

Abstract: Caspian terns Sterna caspia and double-crested cormorants Phalacrocorax auritus that colonize dredge-spoil islands in the Columbia River estuary prey upon millions of juvenile Pacific salmonids annually. We estimated the relative vulnerability of various salmonid stocks to these predators by using data from passive integrated transponder (PIT) tags detected on these colonies; 96,382 tags were detected from the 1998-2000 migration years. On tern colonies, detection rates were highest for tags from steelhead Onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 14 publications
5
99
2
Order By: Relevance
“…From 1993 through 2007, the National Marine Fisheries Service (NMFS) estimated survival for these stocks using detections of PIT-tagged (Prentice et al 1990a) juvenile salmonids passing through Snake River dams and reservoirs Muir et al , 1996Muir et al , 2001aMuir et al ,b, 2003Smith et al , 2000aSmith et al ,b, 2003Smith et al , 2006Hockersmith et al 1999;Zabel et al , 2002Faulkner et al , 2008. In 2008, NMFS completed the sixteenth year of the study.…”
Section: Introductionmentioning
confidence: 99%
“…From 1993 through 2007, the National Marine Fisheries Service (NMFS) estimated survival for these stocks using detections of PIT-tagged (Prentice et al 1990a) juvenile salmonids passing through Snake River dams and reservoirs Muir et al , 1996Muir et al , 2001aMuir et al ,b, 2003Smith et al , 2000aSmith et al ,b, 2003Smith et al , 2006Hockersmith et al 1999;Zabel et al , 2002Faulkner et al , 2008. In 2008, NMFS completed the sixteenth year of the study.…”
Section: Introductionmentioning
confidence: 99%
“…For example, stock-specific variation in the consumption of juvenile salmon by avian predators in the Columbia River estuary has been attributed to stock differences in size, timing, and behavior (Collis et al 2001;Ryan et al 2003;Sebring et al 2013). While there may be conditions under which early timing results in beneficial growth opportunities or survival (Scheuerell et al 2009;Satterthwaite et al 2014), other conditions may select against early timing, leading to survival advantages for later timing (Ryan et al 2003;Beamish et al 2013). Similar advantages and disadvantages also likely occur for variation in fish size (e.g., Willette et al .…”
mentioning
confidence: 99%
“…Each year, thousands of these PIT-tagged fish are consumed by colonial waterbirds and many of the ingested tags are subsequently deposited on piscivorous waterbird colonies throughout the Columbia River basin. The recovery of PIT tags on bird colonies can be used as a measure of predation rates on salmonid ESUs that are listed under the Endangered Species Act (ESA), and these data can be used to assess the relative vulnerability of various salmonid species, stocks, and rearing types to avian predators , Ryan et al 2003. Furthermore, PIT tag recovery data can be used to test hypotheses on the effects of smolt morphology, condition, abundance, and origin on vulnerability to avian predation (see Section 4).…”
Section: Salmonid Predation Rates By Caspian Ternsmentioning
confidence: 99%
“…Data collected as part this research will help regional fishery managers identify and potentially address those intrinsic and extrinsic factors that influence smolt vulnerability to avian predators. Steelhead were selected as the model species for this study because prior research has shown that they are the most vulnerable to predation by birds nesting on the Columbia River Ryan et al 2003;. The benefits of using steelhead for this study are three-fold: (1) we were likely to recover a sufficient number of PIT tags from steelhead on bird colonies along the Columbia River to address a multitude of predation-related questions (more so than any other salmonid species or run), (2) the incidence of morphological abnormalities (e.g., fungal infections, de-scaling, parasites, body injuries, etc.)…”
Section: Section 4: Steelhead Vulnerability Studymentioning
confidence: 99%